2004
DOI: 10.1016/j.pain.2003.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyperalgesic activity of the cox-2 inhibitor lumiracoxib in a model of bone cancer pain in the rat

Abstract: Chronic pain resulting from metastatic bone cancer remains poorly understood and resistant to treatment. Here we have examined the effect of the novel COX-2 enzyme inhibitor lumiracoxib in a model of bone cancer pain in the rat. Lumiracoxib was administered orally twice daily from day 10 to day 20 after injection of MRMT-1 tumour cells into one tibia. Mechanical hyperalgesia, measured as the reduction in weight-bearing of the ipsilateral limb, and the development of static and dynamic allodynia were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 37 publications
2
19
0
1
Order By: Relevance
“…These results have suggested that chronic administration of a COX-2 inhibitor can block prostaglandin synthesis at multiple sites, and may have significant clinical utility in the management of bone cancer and bone cancer pain. A similar reduction in bone cancer pain was observed in mice treated with another COX-2 inhibitor, lumiracoxib (Fox et al, 2004). The same was true for pain control in patients with osteoid osteoma treated with rofecoxib, a selective COX-2 inhibitor (Bottner et al, 2001).…”
Section: Discussionsupporting
confidence: 56%
“…These results have suggested that chronic administration of a COX-2 inhibitor can block prostaglandin synthesis at multiple sites, and may have significant clinical utility in the management of bone cancer and bone cancer pain. A similar reduction in bone cancer pain was observed in mice treated with another COX-2 inhibitor, lumiracoxib (Fox et al, 2004). The same was true for pain control in patients with osteoid osteoma treated with rofecoxib, a selective COX-2 inhibitor (Bottner et al, 2001).…”
Section: Discussionsupporting
confidence: 56%
“…In many of these conditions, there are good animal models that have been used to test potential treatments of central sensitization and allodynia. COX inhibitors [52][53][54], N-methyl-D-aspartate antagonists [55][56][57], antiepileptics [58][59][60], antidepressants [61][62][63], drugs that block nitric oxide production [64], and cannabinoids [65][66][67] show potential in these animal models, but fall short in the clinic. Many of these same classes of drugs are commonly used as preventives in the treatment of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental models studying painful breast cancer tumors have been limited to rat mammary cancer (MRMT-1; refs. 29,30). Development of a murine breast cancer model of bone pain is significant as unique reagents and investigative opportunities using genetically engineered mice are now feasible.…”
Section: Discussionmentioning
confidence: 99%